2018
DOI: 10.1007/s10096-018-3261-3
|View full text |Cite
|
Sign up to set email alerts
|

A host-protein signature is superior to other biomarkers for differentiating between bacterial and viral disease in patients with respiratory infection and fever without source: a prospective observational study

Abstract: Bacterial and viral infections often present with similar symptoms. Etiologic misdiagnosis can alter the trajectory of patient care, including antibiotic overuse. A host-protein signature comprising tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), interferon gamma-induced protein-10 (IP-10), and C-reactive protein (CRP) was validated recently for differentiating bacterial from viral disease. However, a focused head-to-head comparison of its diagnostic performance against other biomarker candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 42 publications
(86 reference statements)
2
64
0
1
Order By: Relevance
“…However, it is difficult to say that IL-6 and IL-8 are more sensitive or specific than CRP or PCT because both poorer and better results have been obtained. Recent studies have shown that IL-6 tests are more sensitive and specific for identifying sepsis in children, but in regards to differential diagnosis of bacterial and viral infections in children with respiratory tract infections or fever without a source, CRP tests are more accurate [ 25 , 46. , 47.…”
Section: Bacterial Protein Biomarkersmentioning
confidence: 99%
“…However, it is difficult to say that IL-6 and IL-8 are more sensitive or specific than CRP or PCT because both poorer and better results have been obtained. Recent studies have shown that IL-6 tests are more sensitive and specific for identifying sepsis in children, but in regards to differential diagnosis of bacterial and viral infections in children with respiratory tract infections or fever without a source, CRP tests are more accurate [ 25 , 46. , 47.…”
Section: Bacterial Protein Biomarkersmentioning
confidence: 99%
“…Thus, to avoid this, tubes with no additives should be used, but the tube of choice should be tested before any clinical studies are performed. In a recent study HNL in serum and plasma was compared to the 3-biomarker algorithm of TRAIL, IP-10, and CRP (25). In that study serum HNL was clearly inferior to the 3-biomarker algorithm and considerably less powerful as compared to other studies on serum.…”
Section: Mini-reviewsmentioning
confidence: 97%
“…A panel of biomarkers should therefore be able to confirm the presence or absence or a microbial infection. It has been reported that isolation and characterization of a panel of host-protein biomarkers yields significantly superior performance for diagnosing bacterial versus viral infections [ 184 ].…”
Section: Immunoaffinity Capillary Electrophoresis Applicationsmentioning
confidence: 99%